Croatia: Growth Slowdown and Policy Alternatives - Vladimir Gligorov; Hermine Vidovic (The Vienna Institute for International Economic Studies (wiiw), 2006)
Having reached a peak in 2002, Croatia's GDP growth lost momentum thereafter due to restrictive economic policy measures prompted by rising external and internal imbalances. The current account deficits, averaging 6-7% of the country's GDP over the past few years, were primarily the consequence of high and growing imbalances in commodity trade which could only be partly offset by earnings from services. Thus, these deficits had to be mainly financed by rising foreign debt, which has been identified as the main threat to macroeconomic stability. In 2004 Croatia, together with Latvia and Estonia, was the most indebted country as compared with the new EU member states and other Southeast European countries. At the beginning of 2005 the World Bank downgraded Croatia to a severely indebted middle-income country'. In addition, Croatia has one of the largest public sectors if compared to the new EU member states or the EU-15, excepting Denmark, France and Sweden. As regards the expenditure structure, the public sector still spends a high portion on public sector wages and salaries, and on subsidies and transfers, as compared to the new EU member states. The high budgetary expenditures have been accompanied by relatively high fiscal deficits. This is especially true for the period following the crisis of the late 1990s. Since then, the reform of public spending has become one of the main economic policy issues. The aim is to bring the deficit gradually down to below 3% of GDP by the year 2007. Also, the government is determined to borrow in domestic rather than foreign currencies in order to diminish the risks associated with the exchange rate and interest rate movements. Croatia's public debt has been on a steady increase in absolute and relative terms over the past couple of years. When compared to the new EU member states, only Hungary exhibits a higher portion than Croatia, while all other countries report much lower levels. Indeed, most of the new member states have managed to reduce their public debt levels over the past few years or to keep them stable. The policy to deal with these macroeconomic imbalances adopted by the government and the central bank on the advice from the IMF in recent years is that of 'soft landing'. In sum, the adopted measures should slow down the growth of aggregate demand and thus lead to slower growth of imports and should stabilize the foreign debt to GDP ratio somewhere around 80% (in euro terms). This policy has brought mixed results so far and it is not clear whether continued reliance on it will be sufficient to move the economy to a path of sustainable growth rather than proving to be just a short-term deviation from the unsustainable growth path. Early in 2005, there were worries that policy is in fact overshooting with growth slowing down faster than expected or desired. Later in the year, growth has speeded up, but the current account deficit has also widened. In any case, the policy adjustment measures that have been introduced will have to be supplemented with longer-term changes and eventually with structural reforms. What are the policy alternatives? Croatia's macroeconomic stability is presumed on the stability of its exchange rate. A problem arises when the exchange rate looks like being misaligned, which is indicated by the unsustainable growth of foreign debt. In that case an adjustment of the exchange rate may be appropriate. If the exchange rate adjustment is not possible because of large balance sheet effects, the alternative would be a more aggressive wage policy. This, however, will largely depend on the assertiveness of the government, which is the main risk of this policy alternative. Another possibility would be more supply-side policies, such as significant changes in the tax system. In a number of countries in transition the corporate tax has been decreased quite significantly. It turns out that a policy of low taxation does not cost the budget too much, because the revenues from the corporate income tax are small anyway, but do create an incentive for foreign investors to locate their operations in these tax havens. This is not a measure that by itself would turn the economy around, but could be considered as a supplement for the economic policy and structural reforms that are difficult to implement immediately. The idea would be to increase investments and growth and introduce structural and public sector reforms in a fast growing economy.
Keywords: E6; F34; H50; H62; O57; 330; Croatia; foreign debt; fiscal deficits; economic policy